Vitamin D Deficiency and Severe Dengue Fever: A Systematic Review and Meta-Analysis - Chuchun Zhuang; Xinxiaodi Yan; Yufeng Liang; Lihua Zhang; Lian Cai; Yukun Lin; Xiaowen Feng; Huacheng Yan (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Vitamin D affects immune function and possibly, dengue severity, but evidence is inconsistent. Observational studies comparing vitamin D levels between severe and nonsevere dengue were systematically searched. A random-effects meta-analysis was conducted. Heterogeneity was quantified using I 2 . Subgroup and sensitivity analyses were performed. Six studies with 1,130 participants were included. The pooled odds ratio (OR) for severe dengue with vitamin D deficiency was 1.77 (95% CI: 0.75–4.16, P = 0.194) with substantial heterogeneity ( I 2 = 61.6%). A subgroup analysis showed a significant association in children (OR: 51.20, 95% CI: 3.12–842.95). Excluding an outlier yielded a significant fixed-effect OR of 1.67 (95% CI: 1.04–2.67, P = 0.034) with reduced heterogeneity ( I 2 = 46.1%). Vitamin D deficiency might be linked to higher odds of severe dengue, especially in children, but confirmation requires larger sample sizes. Establishing causality and assessing vitamin D supplementation in high-risk groups require prospective studies.